Multivariate Based Marker Analysis in Turmeric (Curcuma longa L.) - Vijayalatha, K R; Chezhiyan, N (Journal of Horticultural Sciences, 2008)
Genetic diversity of 30 accessions of turmeric was assessed at the molecular level and compared to morphological traits for degree of divergence. The pattern of clustering of quantitative data based on D2, K means and UPGMA revealed discrepancy among them. The cluster profile, based on quantitative data and RAPD markers exhibited considerable levels of congruence between them. Accessions studied for degree of divergence by RAPD profiles revealed 68.50% polymorphism for 21 primers. The highest number of fragments (10) was obtained with primer OPG 19 while OPC 18 was completely monomorphic. Primers OPB 08, OPC 20, OPE 09 and OPG 19 detected a high level of polymorphism (> 90%). Discrepancy observed at both morphological and molecular levels in the accessions emphasizes the need for specific morphological and molecular markers for discriminating these accessions.